Ti3C2Tx fiber as well as preparation method and application thereof
By forming B-O covalent bond crosslinking between Ti3C2Tx nanosheets, the orientation and density of the nanosheets are improved, and the problem of insufficient conductivity and mechanical strength of the existing Ti3C2Tx fibers is solved, and the Ti3C2Tx fiber with high conductivity and excellent mechanical properties is achieved, which is suitable for wearable electronic systems.
Patent Information
- Application Number
- CN202411938023.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The conductive properties and mechanical strength of existing Ti3C2Tx fibers are far lower than their components, making it difficult to meet the requirements of wearable electronic systems for high conductivity and excellent mechanical properties.
By forming B-O covalent bond crosslinking between Ti3C2Tx nanosheets, the orientation and density of the nanosheets are improved, thereby preparing Ti3C2Tx fibers with high conductivity and excellent mechanical properties.
It realizes the high conductivity and excellent mechanical properties of Ti3C2Tx fibers, and can be continuously removed from the coagulation bath, and is suitable for wearable electronic systems.
Smart Images

Figure CN119615417A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible energy storage materials, and specifically relates to a Ti3C2T x Fiber and its preparation method and application. Background Art
[0002] In recent years, wearable electronic systems, as new portable electronic devices, have been widely used in human-computer interaction, state monitoring, health care and other fields. Conductive fibers have the advantages of light weight, small size and high intelligence, and have become an indispensable basic component in wearable electronic systems. So far, many conductive materials such as carbon-based materials (carbon fiber, carbon nanotubes and graphene, etc.), conductive polymers (polyaniline, polypyrrole and polythiophene, etc.) and metals (silver, copper and stainless steel, etc.) have been used to prepare conductive fibers. However, the above-mentioned conductive fibers still have the problems of limited conductivity and poor mechanical properties, which are difficult to meet the requirements of wearable electronic systems for their high conductivity and excellent mechanical properties. It is urgent to study and prepare new conductive fibers with excellent conductive and mechanical properties.
[0003] Ti3C2T x As an emerging two-dimensional transition metal carbide, it has excellent conductivity (15000S / cm) and excellent mechanical properties (Young's modulus up to 330GPa), and has great potential in the construction of conductive fibers. x The dispersion has liquid crystal properties. By utilizing the pre-arranged orientation characteristics of liquid crystals, Ti3C2T with high conductivity (7748S / cm) and good mechanical strength (40.5MPa) was obtained for the first time through wet spinning process. x Fiber, since then opened the Ti3C2T x Fiber exploration. However, the existing Ti3C2T x The electrical conductivity and mechanical strength of the fiber are much lower than that of its components, which limits the application of Ti3C2T x Application and development of fiber. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a Ti3C2T x Fiber and preparation method and application thereof, the Ti3C2T x Ti3C2T in fiber x The nanosheets have high orientation, high density and low porosity, and have excellent electrical conductivity and mechanical strength.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a Ti3C2T xFibers, including Ti3C2T x Nanosheets, the Ti3C2T x The nanosheets are cross-linked by BO covalent bonds.
[0007] Preferably, the Ti3C2T x Ti3C2T in fiber x The orientation degree of the nanosheets is 0.845-0.852. x The porosity of the fiber is 18.81-20.25%, and the density is 3.05-3.12 g / cm 3 ; The Ti3C2T x The mass percentage of B in the fiber is 0.130-0.152%.
[0008] Preferably, the Ti3C2T x The electrical conductivity of the fiber is 7525-7781 S / cm, the tensile strength is 170.53-188.72 MPa, and the Young's modulus is 45.75-52.42 GPa.
[0009] The present invention also provides the Ti3C2T x The method for preparing the fiber comprises the following steps:
[0010] Ti3C2T x The dispersion of the nanosheets is wet spun, and the resulting spun fibers are coagulated in a coagulation bath in a tetraborate-containing coagulation solution to obtain Ti3C2T x fiber.
[0011] Preferably, the tetraborate-containing coagulation liquid comprises tetraborate and an alcohol aqueous solution; and the tetraborate is sodium tetraborate.
[0012] Preferably, the mass concentration of tetraborate in the tetraborate-containing coagulation liquid is 0.65-0.9 wt %.
[0013] Preferably, the Ti3C2T x The dispersion of Ti3C2T nanosheets x The concentration of the nanosheets is 20 to 30 mg / mL.
[0014] Preferably, the Ti3C2T x The preparation method of the nanosheet comprises the following steps: mixing Ti3AlCl2 powder, LiF and hydrochloric acid, etching in an inert atmosphere, centrifuging and washing the etched mixed solution, dispersing the obtained precipitate in water and shaking, and performing differential centrifugation on the shaken mixed solution to obtain the Ti3C2T x Nanosheets.
[0015] Preferably, the mass ratio of the Ti3AlCl2 powder to LiF is 1:1.5-5; the molar ratio of LiF to HCl in hydrochloric acid is 1:2-6.
[0016] The present invention also provides the Ti3C2T x Fiber or Ti3C2T prepared by the preparation method described in the above technical solution x Applications of fibers in wearable electronic systems.
[0017] The present invention provides a Ti3C2T x Fibers, including Ti3C2T x Nanosheets, the Ti3C2T x The nanosheets are cross-linked by BO covalent bonds. The strong covalent cross-linking of BO covalent bonds (boric acid ester covalent bonds) breaks and replaces the Ti3C2T x The electrostatic repulsion between the nanosheets makes Ti3C2T x Transition from liquid crystal dispersion to macroscopic fibers makes Ti3C2T x The fiber has good mechanical properties and can be continuously taken out from the coagulation bath. The BO covalent bond length is short and the structure is stable, which not only reduces the x Ti3C2T inside the fiber x The spacing of the nanosheets also increases the Ti3C2T x The orientation and density of the nanosheets have led to the realization of Ti3C2T x Optimal load transfer between nanosheets greatly improves the Ti3C2T x Mechanical properties of fibers; Ti3C2T x The reduced spacing and close stacking of nanosheets improve the inter-sheet contact efficiency and contribute to the x A continuous electron transmission path is formed inside the fiber, allowing electrons to travel through the Ti3C2T x The nanosheets move in a more consistent and efficient manner, reducing electron scattering and improving the performance of Ti3C2T x The electrical conductivity of the nanosheet fibers makes Ti3C2T x The fibers have high electrical conductivity and excellent mechanical properties.
[0018] The present invention also provides the Ti3C2T x Preparation method of Ti3C2T fiber x Ti3C2T in liquid crystal dispersion x The nanosheets are locally oriented and not aggregated, which helps Ti3C2T x Ti3C2T nanostructured nanostructures were prepared by wet spinning of dispersions of Ti3C2T nanostructured nanostructures without additives or polymers. xThe coagulation liquid containing tetraborate is used as the coagulation bath, and the tetraborate and Ti3C2T x The surface hydroxyl functional groups form strong covalent crosslinks of BO covalent bonds (boric acid ester covalent bonds). The chemical crosslinking process breaks and replaces the Ti3C2T x The electrostatic repulsion between the nanosheets makes Ti3C2T x The transition from liquid crystal dispersion to macroscopic fibers not only helps Ti3C2T x The continuous generation of fibers also makes Ti3C2T x The fibers have good mechanical properties and can be continuously removed from the coagulation bath. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 For Ti3AlC2 and Ti3C2T in Example 1 x X-ray diffraction spectrum (a) and X-ray photoelectron spectrum (b) of the nanosheets;
[0020] Figure 2 Ti3C2T prepared in Example 1 x Polarized light microscope photo of the nanosheet;
[0021] Figure 3 Ti3C2T prepared in Example 1 x photos of the fibers being wound onto bobbins and of the weaving;
[0022] Figure 4 Ti3C2T prepared in Example 1 x Scanning electron micrograph of the fibers;
[0023] Figure 5 Ti3C2T prepared in Example 1 x and Ti3C2T x Fourier transform infrared spectra of the fibers;
[0024] Figure 6 Ti3C2T prepared in Example 1 and Comparative Examples 1 to 4 x density and porosity plots of fibers;
[0025] Figure 7 Ti3C2T prepared in Example 1 and Comparative Examples 1 to 4 x Fiber orientation diagram. DETAILED DESCRIPTION
[0026] The present invention provides a Ti3C2T x Fibers, including Ti3C2T x Nanosheets, the Ti3C2T x The nanosheets are cross-linked by BO covalent bonds.
[0027] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0028] As an embodiment, the Ti3C2T x Ti3C2T in fiber x The orientation degree of the nanosheets is 0.845-0.852, and is 0.852 in a specific embodiment; the Ti3C2T x The porosity of the fiber is 18.81-20.25%, and in the specific embodiment is 18.81%, and the density is 3.05-3.12 g / cm 3 , in the specific embodiment, 3.12 g / cm 3 , with a diameter of 22 to 24 μm, and 23 μm in a specific embodiment; the Ti3C2T x The mass percentage of B in the fiber is 0.130-0.152%, and in the specific embodiment, it is 0.142%.
[0029] As an embodiment, the Ti3C2T x The electrical conductivity of the fiber is 7525-7781 S / cm, 7781 S / cm in the specific embodiment, the tensile strength is 170.53-188.72 MPa, 188.72 MPa in the specific embodiment, and the Young's modulus is 45.75-52.42 GPa, 52.42 GPa in the specific embodiment.
[0030] The present invention also provides the Ti3C2T x The method for preparing the fiber comprises the following steps:
[0031] Ti3C2T x The dispersion of the nanosheets is wet spun, and the resulting spun fibers are coagulated in a coagulation bath in a tetraborate-containing coagulation solution to obtain Ti3C2T x fiber.
[0032] The present invention converts Ti3C2T x The dispersion of the nanosheets is wet-spun to obtain spun fibers.
[0033] Ti3C2T x Nanosheets T x Represents various surface functional groups on the nanosheets, such as -OH and -F.
[0034] As an embodiment, the Ti3C2T xThe preparation method of the nanosheet comprises the following steps: mixing Ti3AlCl2 powder, LiF and hydrochloric acid, etching in an inert atmosphere, centrifuging and washing the etched mixed solution, dispersing the obtained precipitate in water and shaking, and performing differential centrifugation on the shaken mixed solution to obtain the Ti3C2T x Nanosheets.
[0035] As an embodiment, the particle size of the Ti3AlCl2 powder is 1 to 40 μm, and in a specific embodiment, it is 5 to 20 μm; the mass ratio of the Ti3AlCl2 powder to LiF is 1:1.5 to 5, and in a specific embodiment, it is 1:1.6 to 3; the molar ratio of LiF to HCl in hydrochloric acid is 1:2 to 6, and in a specific embodiment, it is 1:2.9 to 4.9; the concentration of the hydrochloric acid is 6 to 9 mol / L, and in a specific embodiment, it is 7 to 9 mol / L; the inert atmosphere is argon; after argon is introduced into the dispersion obtained by mixing the Ti3AlCl2 powder, LiF and hydrochloric acid, the container is sealed with plastic wrap; the etching is carried out under stirring; the stirring rate is 500 to 1000 rpm, and in a specific embodiment, it is 800 to 1000 rpm; the etching temperature is 40 to 50°C, and in a specific embodiment, it is 50°C; the etching time is 36 to 48 hours, and in a specific embodiment, it is 48 hours.
[0036] As an implementation mode, Ti3AlCl2 powder, LiF and hydrochloric acid are mixed as follows: LiF is first added to hydrochloric acid and stirred until completely dissolved, and then Ti3AlCl2 powder is added; the stirring rate is 500-1000rpm, and in a specific embodiment, it is 800-1000rpm; the stirring time is 20-30min, and in a specific embodiment, it is 30min; the addition of Ti3AlCl2 powder is to add Ti3AlCl2 powder slowly and multiple times.
[0037] During the etching process, HF etching is mainly used. LiF and HCl first generate HF, which etches the Al layer of the Ti3AlC2 phase to generate Ti3C2 and H2. Since Ti3C2 is not stable, it will continue to combine with H2O and HF to generate Ti3C2(OH)2 and Ti3C2F2, while releasing H2.
[0038] The reaction equation involved in the etching process is as follows:
[0039] Ti3AlC2+3HF→AlF3+3 / 2H2+Ti3C2
[0040] Ti3C2+2H2O→Ti3C2(OH)2+H2
[0041] Ti3C2+2HF→Ti3C2F2+H2.
[0042] The present invention uses HF generated by the reaction of LiF and HCl to etch Ti3AlCl2 to prepare Ti3C2T x Compared with direct HF etching of Ti3AlCl2, the nanosheet method has a mild reaction and is environmentally friendly.
[0043] As an embodiment, the centrifugal washing is performed until the washing waste liquid is neutral; the reagent used for the centrifugal washing is water, and in a specific embodiment, it is deionized water; the number of centrifugal washings is 7 to 9 times, and in a specific embodiment, it is 8 times; the centrifugal speed of each centrifugal washing is 3500 to 5000 rpm, and in a specific embodiment, it is 3500 to 4000 rpm; the time of each centrifugal washing is 5 to 10 minutes, and in a specific embodiment, it is 5 to 8 minutes; the neutrality is pH = 7; the water is deionized water; the present invention has no special limitation on the oscillation method, and the oscillation method well known in the art can be used. In the embodiment of the present invention, the oscillation The method comprises the following steps: the first step is to perform a low-speed centrifugation, and the second step is to perform a high-speed centrifugation on the supernatant obtained by the low-speed centrifugation; the low-speed centrifugation rate is 1000-1500 rpm, and the specific embodiment is 1500 rpm; the low-speed centrifugation time is 30-40 min, and the specific embodiment is 30 min; the high-speed centrifugation rate is 4500-5000 rpm, and the specific embodiment is 4500 rpm; the high-speed centrifugation time is 10-20 min, and the specific embodiment is 20 min; the Ti3C2T x The nanosheets are stored in an inert atmosphere and a low temperature environment to prevent oxidation; the inert atmosphere is argon; and the low temperature is 0°C.
[0044] The present invention prepares Ti3C2T with a certain size by "LiF / HCl etching-differential centrifugation" x Nanosheets, and then prepare Ti3C2T x The dispersion of nanosheets is used for spinning. In the present invention, the mixed solution obtained after etching contains broken Ti3C2T x Nanosheets, required Ti3C2T x Nanosheets and unetched or incompletely etched Ti3AlCl2, the present invention obtains the desired Ti3C2T by differential centrifugation x Nanosheets.
[0045] As an embodiment, the Ti3C2T x The preparation method of the dispersion of nanosheets is as follows: x The nanosheets were dispersed in water to obtain the Ti3C2T xThe dispersion of nanosheets; the water is deionized water.
[0046] As an embodiment, the Ti3C2T x The dispersion of Ti3C2T nanosheets x The concentration of the nanosheets is 20-30 mg / mL, and in a specific embodiment is 25 mg / mL.
[0047] As an embodiment, the equipment used for wet spinning includes a syringe with a nozzle and a syringe pump; the inner diameter of the syringe nozzle is 200 μm; and the push speed of the syringe pump is 3.6 mL / h.
[0048] Before the wet spinning, the present invention further comprises: x The dispersion of nanosheets is placed in a syringe with a nozzle and then emptied; the emptying is to use the syringe plunger to push the Ti3C2T x The dispersion of nanosheets is slightly squeezed out of the nozzle, and the air in the syringe is squeezed out. x The syringe of the nanosheet dispersion is emptied to prevent the presence of air from breaking the fibers during fiber extrusion.
[0049] After obtaining the spun fiber, the present invention performs coagulation bath coagulation of the spun fiber in a coagulation solution containing tetraborate to obtain Ti3C2T x fiber.
[0050] As an embodiment, the tetraborate-containing coagulation liquid includes tetraborate and an alcohol aqueous solution; the tetraborate is sodium tetraborate; the alcohol aqueous solution includes water and ethanol; the water is deionized water; the mass ratio of water to ethanol is 7:3; the preparation method of the tetraborate-containing coagulation liquid includes the following steps: mixing the tetraborate and water, stirring until dissolved, and then adding ethanol; the stirring rate is 500-1000rpm, and in a specific embodiment, it is 800-1000rpm. The sodium tetraborate material used in the present invention has a wide source and low cost.
[0051] As an embodiment, the mass concentration of tetraborate in the tetraborate-containing coagulation liquid is 0.65-0.9wt%, and in a specific embodiment, it is 0.75wt%.
[0052] As an embodiment, the coagulation bath coagulation is carried out under the condition of rotation; the rotation speed is 9.42 mm / s; the device used for the rotation is a rotating turntable; during the rotation process, the container containing the tetraborate coagulation liquid is placed in the center of the rotating turntable to ensure that the Ti3C2T xThe fibers are subjected to uniform force; after the wet spinning is completed, the present invention further comprises: slowly reducing the rotation speed to avoid reducing the rotation speed too quickly and causing Ti3C2T x The fibers are tangled together and not easy to collect; slowly reduce the rotation speed to 0.1 mm / s 2 The rate reduces the speed of rotation. At the above rotation speed, the spinning fiber can be spun continuously without breaking.
[0053] As an embodiment, after the coagulation bath is coagulated, the method further comprises: immersing the spun fiber coagulated by the coagulation bath in the coagulation liquid containing tetraborate, separating the solid and the liquid, and washing, collecting and drying the obtained solid in sequence to obtain Ti3C2T x fiber; the soaking time is 10 to 20 minutes, and in a specific embodiment, it is 10 to 15 minutes; the washing times are 2 to 5 times, and in a specific embodiment, it is 3 times; the washing liquid used for washing is an alcohol aqueous solution; the alcohol aqueous solution includes water and ethanol; the water is deionized water; the mass ratio of water to ethanol is 7:3; the collection is drum collection; the drying is carried out at room temperature, and in a specific embodiment, it is 25°C; the drying time is 20 to 40 minutes, and in a specific embodiment, it is 30 minutes; the drying is carried out in air; the Ti3C2T x The fibers were stored under vacuum to prevent oxidation.
[0054] The present invention further immerses the spun fibers after coagulation in the coagulation bath in the coagulation solution containing tetraborate, so as to better bind the tetraborate to Ti3C2T x Reaction of hydroxyl groups on nanosheets.
[0055] The present invention adjusts Ti3C2T x The concentration of the nanosheet dispersion is such that Ti3C2T x The nanosheets are locally oriented and not aggregated, which helps Ti3C2T x Nanosheets were prepared by direct wet spinning of Ti3C2T nanosheets without additives or polymers. x Fiber. Then Ti3C2T x The dispersion of nanosheets was used as the spinning solution, and the coagulation solution containing tetraborate was used as the coagulation bath to prepare Ti3C2T3 with high conductivity and excellent mechanical properties through wet spinning process. x Fiber. Tetraborate and Ti3C2T during wet spinning x The hydroxyl groups on the Ti3C2T4O4 form stable BO covalent bonds (boric acid ester covalent bonds), and this chemical crosslinking process breaks and replaces the Ti3C2T4O4O4 x The electrostatic repulsion between the nanosheets makes Ti3C2T xThe transition from liquid crystal dispersion to macroscopic fibers not only helps Ti3C2T x The continuous generation of gel fibers also makes Ti3C2T x The gel fibers have good mechanical properties and can be continuously taken out from the coagulation bath. This strong covalent crosslinking also reduces the x Ti3C2T inside the fiber x Nanosheet spacing, which simultaneously increases the Ti3C2T x The orientation and density of the nanosheets significantly enhance the x The load transfer between the sheets greatly improves the Ti3C2T x It improves the mechanical properties of the fiber; it also helps to form a continuous electron transmission path inside the fiber, and enables electrons to move between sheets in a more consistent and efficient manner, reducing electron scattering and improving fiber conductivity.
[0056] The present invention also provides the Ti3C2T x Fiber or Ti3C2T prepared by the preparation method described in the above technical solution x Applications of fibers in wearable electronic systems.
[0057] The present invention relates to the Ti3C2T x There is no particular limitation on the application of the fiber in the wearable electronic system, and any application method known in the art may be used.
[0058] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0059] Example 1
[0060] 1.6 g LiF was added to 20 mL of 9 mol / L hydrochloric acid, stirred at 1000 rpm for 30 min until completely dissolved, and then 1.0 g Ti3AlCl2 powder (particle size of 1-40 μm) was slowly added several times. After argon was introduced into the obtained dispersion, the container was sealed with plastic wrap, and the mixture was stirred at 800 rpm for 48 h at 50 ° C in an argon atmosphere for etching. After the reaction was completed, the mixed solution was repeatedly centrifuged and washed 8 times with deionized water until the pH of the obtained washing solution was 7, each time at 3500 rpm for 5 min, and the obtained sediment was dispersed in deionized water and continuously shaken for 20 min. Then, the shaken mixed solution was centrifuged at 1500 rpm for 30 min, and the supernatant was centrifuged at 4500 rpm for 20 min to collect the sediment to obtain Ti3C2T x Nanosheets;
[0061] Sodium tetraborate (Na2B4O7) and deionized water are mixed and stirred at 1000 rpm until dissolved, and then ethanol is added to obtain a tetraborate-containing coagulation liquid, wherein the mass concentration of sodium tetraborate in the tetraborate-containing coagulation liquid is 0.75%, and the mass ratio of deionized water to ethanol is 7:3;
[0062] The Ti3C2T x The nanosheets were dispersed in deionized water to obtain a Ti3C2T3O4 nanosheet with a concentration of 25 mg / mL. x The dispersion of nanosheets was placed in a syringe with a nozzle of 200 μm in inner diameter as a spinning solution, and the Ti3C2T x The dispersion of nanosheets was slightly squeezed out of the nozzle, and the air in the syringe was squeezed out. The injection pump speed was 3.6 mL / h, and the Ti3C2T x The dispersion of nanosheets is extruded through a nozzle into the tetraborate-containing coagulation solution for coagulation in a coagulation bath. The container containing the tetraborate-containing coagulation solution is placed in the center of a rotating turntable and rotated at 9.42 mm / s. The spinning fibers are formed immediately after contacting the tetraborate-containing coagulation solution and are continuously generated as the rotation is completed. After the wet spinning is completed, the spinning fibers are rotated at 0.1 mm / s. 2 The rotation speed is reduced at a rate, and the spun fibers after coagulation in the coagulation bath are immersed in the tetraborate-containing coagulation solution for 10 minutes, and then the solid-liquid separation is performed. The obtained solid is washed three times with a washing solution composed of deionized water and ethanol in a mass ratio of 7:3. The washed spun fibers are collected on a drum and dried in air at 25°C for 30 minutes to obtain Ti3C2T x fiber.
[0063] Example 2
[0064] The difference from Example 1 is that the Ti3C2T prepared in Example 1 x The spun fibers obtained by wet spinning the dispersion of the nanosheets are coagulated in a coagulation bath in a tetraborate-containing coagulation solution with a mass concentration of sodium tetraborate of 0.65%. The rest of the contents are the same as in Example 1.
[0065] Example 3
[0066] The difference from Example 1 is that the Ti3C2T prepared in Example 1 x The spun fibers obtained by wet spinning the dispersion of the nanosheets are coagulated in a coagulation bath in a tetraborate-containing coagulation solution with a mass concentration of sodium tetraborate of 0.9%, and the rest of the contents are the same as in Example 1.
[0067] Comparative Example 1
[0068] The difference from Example 1 is that the Ti3C2T prepared in Example 1 xThe spun fibers obtained by wet spinning the dispersion of the nanosheets are coagulated in a coagulation bath in a tetraborate-containing coagulation solution with a mass concentration of sodium tetraborate of 0.25%. The rest of the contents are the same as in Example 1.
[0069] Comparative Example 2
[0070] The difference from Example 1 is that the Ti3C2T prepared in Example 1 x The spun fibers obtained by wet spinning the dispersion of the nanosheets are coagulated in a coagulation bath in a tetraborate-containing coagulation solution with a mass concentration of sodium tetraborate of 0.5%, and the rest of the contents are the same as in Example 1.
[0071] Comparative Example 3
[0072] The difference from Example 1 is that the Ti3C2T prepared in Example 1 x The spun fibers obtained by wet spinning the dispersion of the nanosheets are coagulated in a coagulation bath in a tetraborate-containing coagulation solution with a mass concentration of 1% sodium tetraborate, and the rest of the contents are the same as in Example 1.
[0073] Comparative Example 4
[0074] The difference from Example 1 is that the Ti3C2T prepared in Example 1 x The spun fibers obtained by wet spinning the dispersion of the nanosheets are coagulated in a coagulation bath in a tetraborate-containing coagulation solution with a mass concentration of sodium tetraborate of 1.25%. The rest of the contents are the same as in Example 1.
[0075] Comparative Example 5
[0076] The difference from Example 1 is that the Ti3C2T prepared in Example 1 x The spun fibers obtained by wet spinning the dispersion of nanosheets were coagulated in a coagulation bath in a tetraborate-containing coagulation solution with a mass concentration of 0% sodium tetraborate, and the rest of the contents were the same as in Example 1. Ti3C2T x It is even more impossible to take it out of the coagulation bath and dry it to obtain Ti3C2T x fiber.
[0077] Performance Testing
[0078] (1) Ti3C2T prepared in Example 1 and Comparative Examples 1 to 4 x The properties of the fibers were tested and the results are shown in Table 1.
[0079] Table 1 Ti3C2T prepared in Example 1 and Comparative Examples 1 to 4 x Fiber performance test results
[0080] project Conductivity (S / cm) Tensile strength(MPa) Young's modulus(GPa) Example 1 7781 188.72 52.42 Comparative Example 1 6407 74.40 16.91 Comparative Example 2 7206.67 130.31 31.78 Comparative Example 3 7340 139.83 43.7 Comparative Example 4 6644 95.52 32.94
[0081] It can be seen from Table 1 that the Ti3C2T prepared in the embodiment of the present invention x The electrical conductivity, tensile strength and Young's modulus of the fiber are significantly higher than those of the control group. It can be seen that the content of tetraborate in the tetraborate-containing coagulant will affect the properties of Ti3C2T x The number of BO covalent bonds in the fiber affects the Ti3C2T x Ti3C2T in fiber x The orientation and density of nanosheets affect their electrical conductivity and mechanical properties.
[0082] (2) Figure 1 For Ti3AlC2 and Ti3C2T in Example 1 x (a) X-ray diffraction spectrum and (b) X-ray photoelectron spectrum of the nanosheets.
[0083] Depend on Figure 1 As shown in (a), the two main characteristic peaks of Ti3AlC2 are located at 9.46° and 38.7°, corresponding to the (002) and (104) crystal planes of Ti3AlC2, respectively. x The (104) peak belonging to Ti3AlC2 disappears, and the (002) peak moves from 9.46° of Ti3AlC2 to 7.48°, which confirms that the Al layer is successfully etched. In addition, the Ti3AlC2 and Ti3C2T calculated according to the Bragg formula x The interlayer spacings of Li + The intercalation effect of ions increases the x The layer spacing.
[0084] from Figure 1 As shown in (b), the characteristic absorption peaks of Ti 3p, Ti 3s, Al 2p, Al 2s, C 1s, Ti 2p and O 1s exist in Ti3AlC2 at 35eV, 60eV, 74eV, 119eV, 285eV, 457eV and 531eV, respectively, indicating that Ti3AlC2 mainly contains four atoms: Ti, Al, C and O. After strong acid etching, Ti3C2T x The Al 2p and Al 2s peaks of Ti3C2T x It mainly contains four atoms: Ti, C, O and F.
[0085] (3) Figure 2 Ti3C2T prepared in Example 1 x Polarized light microscope image of the nanosheet.
[0086] Depend on Figure 2 It can be seen that Ti3C2Tx The birefringence of the dispersion formed by the nanosheets is very obvious and uniform, indicating that the Ti3C2T x The dispersion completely changes from isotropic to anisotropic, Ti3C2T x The internal local orientation and no aggregation are very important in assembling Ti3C2T x Macrostructure, especially the Ti3C2T3 aligned sheets prepared by wet spinning x Fiber has unique advantages.
[0087] (3) Figure 3 Ti3C2T prepared in Example 1 x Photos of fibers wound on bobbins and braided, where (a) is Ti3C2T x Photos of fibers wound on bobbins, (b) and (c) are Ti3C2T x Photo of the weaving of fibers.
[0088] Depend on Figure 3 As can be seen in (a), Ti3C2T x Fibers can be produced continuously and with uniform size.
[0089] Depend on Figure 3 As can be seen from (b) and (c), Ti3C2T x The fibers have good mechanical properties and can be manually woven into textiles.
[0090] (4) Figure 4 Ti3C2T prepared in Example 1 x Scanning electron micrograph of the fiber, where (a) is Ti3C2T x Overall scanning electron micrograph of the fiber, (b) is Ti3C2T x Scanning electron micrograph of the cross section of the fiber, (c) is Ti3C2T x Scanning electron micrograph of the fiber surface.
[0091] Depend on Figure 4 As can be seen in (a), Ti3C2T x The average diameter of the fibers was 23 μm.
[0092] Depend on Figure 4 As can be seen in (b), the Ti3C2T x The nanosheets are highly aligned and densely packed along the fiber axis, indicating that the locally ordered Ti3C2T x The nanosheets are aligned under the shearing action of the fine nozzle and the interfacial cross-linking action.
[0093] Depend on Figure 4It can be seen from (c) that during the drying process, due to the x The fiber shrinkage gives it a wrinkled surface morphology.
[0094] (5) Figure 5 Ti3C2T prepared in Example 1 x and Ti3C2T x Fourier transform infrared spectrum of the fiber.
[0095] Depend on Figure 5 It can be seen that Ti3C2T x At 3426cm -1 and 1663cm -1 The characteristic peaks of Ti3C2T are attributed to the typical stretching vibrations of -OH and C=O. x Fiber at 3426cm -1 The decrease of -OH peak intensity at 1168 cm -1 The appearance of BO characteristic peaks further proves that Ti3C2T x Ti3C2T in fiber x The nanosheets are covalently cross-linked by borate covalent bonds (BO covalent bonds).
[0096] (6) Figure 6 Ti3C2T prepared in Example 1 and Comparative Examples 1 to 4 x Density and porosity diagram of fibers.
[0097] Depend on Figure 6 It can be seen that when the concentration of Na2B4O7 increases from 0.25wt% to 0.75wt%, Ti3C2T x The porosity of the fiber decreased significantly from 34.27±2.98% to 18.81±1.82%, and the density decreased from 2.43±0.11 g / cm 3 Increased to 3.12±0.07g / cm 3 More than 0.75wt% Na2B4O7 may lead to Ti3C2T x The wrinkles and intersheet spaces of the nanosheets increased, the fiber porosity increased, and the fiber density decreased.
[0098] (7) Figure 7 Ti3C2T prepared in Example 1 and Comparative Examples 1 to 4 x Fiber orientation diagram.
[0099] Depend on Figure 7 It can be seen that as the concentration of Na2B4O7 increases from 0.25wt% to 0.75wt%, the orientation degree increases from 0.815 to 0.852. This indicates that Ti3C2T xThe stable boron-oxygen tetrahedral structure formed between sheets can effectively improve the fiber sheet arrangement and promote the high orientation of the sheets. However, as the Na2B4O7 concentration further increases to 1.25wt%, the Ti3C2T x The full width at half maximum (FWHM) of the fibers became wider and the degree of orientation decreased from 0.852 to 0.822, indicating that the excessive borate covalent bonds (BO covalent bonds) were not conducive to the effective alignment of nanosheets in the fibers.
[0100] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A Ti3C2T x Fiber, characterized in that Including Ti3C2T arranged in liquid crystal orientation x Nanosheets, the Ti3C2T x The nanosheets are cross-linked by BO covalent bonds.
2. Ti3C2T according to claim 1 x Fiber, characterized in that The Ti3C2T x Ti3C2T in fiber x The orientation degree of the nanosheets is 0.845-0.
852. x The porosity of the fiber is 18.81-20.25%, and the density is 3.05-3.12 g / cm 3 ; The Ti3C2T x The mass percentage of B in the fiber is 0.130-0.152%.
3. Ti3C2T according to claim 1 or 2 x Fiber, characterized in that The Ti3C2T x The electrical conductivity of the fiber is 7525-7781 S / cm, the tensile strength is 170.53-188.72 MPa, and the Young's modulus is 45.75-52.42 GPa.
4. The Ti3C2T3 according to any one of claims 1 to 3 x The method for preparing a fiber is characterized in that: The following steps are involved: Ti3C2T x The dispersion of the nanosheets is wet spun, and the resulting spun fibers are coagulated in a coagulation bath in a tetraborate-containing coagulation solution to obtain Ti3C2T x fiber.
5. The preparation method according to claim 4, characterized in that: The tetraborate-containing coagulation liquid comprises tetraborate and an alcohol aqueous solution; the tetraborate is sodium tetraborate.
6. The preparation method according to claim 4 or 5, characterized in that: The mass concentration of tetraborate in the tetraborate-containing coagulation liquid is 0.65-0.9 wt %.
7. The preparation method according to claim 4, characterized in that: The Ti3C2T x The dispersion of Ti3C2T nanosheets x The concentration of the nanosheets is 20 to 30 mg / mL.
8. The preparation method according to claim 4 or 7, characterized in that: The Ti3C2T x The preparation method of the nanosheet comprises the following steps: mixing Ti3AlCl2 powder, LiF and hydrochloric acid, etching in an inert atmosphere, centrifuging and washing the etched mixed solution, dispersing the obtained precipitate in water and shaking, and performing differential centrifugation on the shaken mixed solution to obtain the Ti3C2T x Nanosheets.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the Ti3AlCl2 powder to LiF is 1:1.5-5; the molar ratio of LiF to HCl in hydrochloric acid is 1:2-6.
10. The Ti3C2T3 according to any one of claims 1 to 3 x Fiber or Ti3C2T prepared by the preparation method according to any one of claims 4 to 9 x Applications of fibers in wearable electronic systems.
Citation Information
Patent Citations
Preparation method of densified titanium carbide composite film
CN113582591A
MXene aerogel fiber as well as preparation method and application thereof
CN113718371A
MXene fiber non-woven fabric and preparation method thereof
CN115538209A
Preparation method of synergistically densified titanium carbide composite film
CN115818644A
Anode active material, composition for anode including the same, and secondary battery preparing the same
KR1020220169155A
Cited By
Electromagnetic shielding flame-retardant fabric and preparation method thereof
CN120537118A
Electromagnetic shielding flame resistant fabric and method of making same
CN120537118B